Contingency management treatment in cocaine using methadone maintained patients with and without legal problems. (1st November 2017) - Ginley, Meredith K.; Rash, Carla J.; Olmstead, Todd A.; Petry, Nancy M.
Highlights: Legal problems at study baseline were inversely related to substance use outcomes. Contigency management improved substance use outcomes regardless of legal problems. Contigency management reduced continuing with illegal activities through follow-up. Abstract: Background: Legal difficulties and cocaine use are prevalent in methadone maintenance patients, and they are related to one another, as well as to poor response to methadone treatment. Contingency management (CM) is efficacious for decreasing cocaine use, but the relation of CM treatment to criminal activities has rarely been studied. Methods: This study evaluated whether baseline legal problems are related to subsequent substance use and illegal activities for cocaine using methadone maintained patients and whether CM differentially improves outcomes depending on baseline legal problems. Using data from four randomized CM trials ( N = 323), we compared methadone maintained patients with legal problems at the start of study participation to those without initial legal problems. Results: Overall, the addition of CM to standard methadone care improved substance use outcomes regardless of initial legal problems. Endorsement of legal problems within 30 days of study initiation was associated with reduced proportion of negative samples submitted during the 12-week treatment period. A significant interaction effect of baseline legal problems and treatment condition was present for subsequent self-reports of illegal activities. Those with baseline legal problems who were assigned to CM had reduced self-reports of reengagement in illegal activity throughout a six month follow-up compared to their counterparts randomized to standard care. Conclusions: Adding CM to methadone treatment improves substance use outcomes and reduces subsequent illegal activity in cocaine-using methadone patients with legal problems.